Intangible Assets, Bonus Mechanism, Debt Covenant, and Transfer Pricing: Moderating Role of Board Gender Diversity - Dila Dwi Hastuti; Badingatus Solikhah (SENTRALISASI, 2026)
This study examines the effects of intangible assets, bonus mechanisms, and debt covenants on transfer pricing and the moderating role of board gender diversity. Using panel data from 840 non-financial companies listed on the Indonesia Stock Exchange during 2020–2024 (4,200 firm-year observations), the analysis employs panel data regression. This study offers two main novelties. First, while most prior studies focus on direct determinants of transfer pricing, existing literature rarely examines board gender diversity as a moderating variable in the relationships between intangible assets, bonus mechanisms, debt covenants, and transfer pricing. Second, this study uses a comprehensive sample of all non-financial companies, providing more representative evidence of transfer pricing practices in Indonesia. The results show that intangible assets, bonus mechanisms, and debt covenants have a significant positive effect on transfer pricing. Board gender diversity weakens the influence of intangible assets and debt covenants, suggesting enhanced monitoring and governance effectiveness, but strengthens the effect of bonus mechanisms, indicating that incentive-driven performance pressures may override governance controls. The findings contribute to the transfer pricing and corporate governance literature by demonstrating the dual role of board gender diversity. Practically, the results provide insights for regulators, tax authorities, and companies in designing governance mechanisms and compensation policies to mitigate transfer pricing risks. Future research is encouraged to incorporate additional variables, apply more comprehensive measures of gender diversity, and use more detailed transfer pricing documentation.